Contingent capital short-term investors and the evolution of corporate governance in France and Germany - Goyer, Michel (Oxford : Oxford University Press, 2011)
Will the pressures of financial market globalization force companies to converge on a shareholder-based model of corporate governance? In 'Contingent Capital', Michel Goyer highlights the importance of the institutional context, in which companies are embedded.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Institutional investments -- France; Institutional investments -- Germany; Capital movements -- France; Capital movements -- Germany; Corporate governance -- France; Corporate governance -- Germany